2011
DOI: 10.1002/ijc.26291
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of one‐step nucleic acid amplification for intraoperative sentinel node metastasis detection in breast cancer patients

Abstract: The purpose of this prospective multicenter study was to assess one-step nucleic acid amplification (OSNA) for intraoperative sentinel lymph node (SLN) metastasis detection in breast cancer patients, using final histology as the reference standard. OSNA results were also compared to intraoperative histology SLN evaluation and to standard clinicopathological risk markers. For this study, fresh SLNs were cut in four blocks, and alternate blocks were used for OSNA and histology. CK19 mRNA copy number was categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 37 publications
3
38
0
4
Order By: Relevance
“…24 The cost for the total patient population was V362,664. Intraoperative histological examinations are less effective 4,6 and significantly increase treatment costs for patients operated on for early breast cancer.…”
mentioning
confidence: 99%
“…24 The cost for the total patient population was V362,664. Intraoperative histological examinations are less effective 4,6 and significantly increase treatment costs for patients operated on for early breast cancer.…”
mentioning
confidence: 99%
“…The study by Le Frère-Belda et al 58 reported a sensitivity of 91.1% (95% CI 80.3% to 97.1%) and a specificity of 97.2% (95% CI 95.1% to 98.6%) for OSNA compared with five-level histology after adjustment for TAB.…”
Section: Single-gate Studiesmentioning
confidence: 98%
“…Sixteen test accuracy papers were included for OSNA, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] with two papers reporting the same study. Two unpublished papers 40,66 for Metasin were identified and assessed using the Standards for the Reporting of Diagnostic Accuracy Studies (STARD) in Table 7.…”
Section: Number and Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations